Infection of Helicobacter pylori contributes to the progression of gastric cancer through ferroptosis - Yun Liu; Renjie Miao; Jinxuan Xia; Yong Zhou; Jun Yao; Shihe Shao (Cell Death Discovery)
Abstract Helicobacter pylori (H. pylori) is a gram-negative pathogen that colonizes gastric epithelial cells, and its chronic infection is the primary risk factor for the development of gastric cancer (GC). Ferroptosis is an iron-dependent form of cell death characterized by intracellular lipid peroxide accumulation and reactive oxygen species (ROS) imbalance. There is evidence suggesting that pathogens can manipulate ferroptosis to facilitate their replication, transmission, and pathogenesis. However, the interaction between ferroptosis and H. pylori infection requires further elucidation. We reviewed the mechanism of ferroptosis and found that H. pylori virulence factors such as cytotoxin-associated gene A (CagA), vacuolating cytotoxin A (VacA), neutrophil-activating protein A (NapA), superoxide dismutase B (SodB), γ-glutamyl transpeptidase (gGT), lipopolysaccharide (LPS), and outer inflammatory protein A (OipA) affected glutathione (GSH), ROS, and lipid oxidation to regulate ferroptosis. It also affected the progression of GC by regulating ferroptosis-related indicators through abnormal gene expression after H. pylori infected gastric mucosa cells. Finally, we discuss the potential application value of ferroptosis inducers, inhibitors and other drugs in treating H. pylori-infected GC patients while acknowledging that their interactions are still not fully understood.